Conceptualizing organizational learning system model and innovativeness - Arumugam, Thilageswary; Idris, Khairuddin; Munusamy, Komathi (Center for Promoting Ideas, 2015)
The link between organizational learning, organizational innovativeness and performance is very profound in the literature. Organizational Learning Systems Model (OLSM) focuses on organizational learning as a social organization and how it learns to exist in the surroundings. Emphasis on organization learning based like Parsons general theory of social action has linked performance and learning element in order to evaluate organizational performance. The Organizational Learning Systems Model (OLSM) grounded from Parsonian social system perspective which is active in nature help identifies the importance of working and learning process of adjustment. Organizational learning here is drawn from behavioural dimensions; acquiring knowledge, distributing and interpreting data, and organizational memory. Evidence has indicated that organizational performance increases when learning happens in an organization. Organizational innovativeness has shown the relationship with learning. This subject tries to evaluate the relationship between organizational learning systems model, organizational innovativeness that leads to positive output for the system.